Simulations of arbitrary crack path deflection at a material interface in layered structures. (June 2015) - Tambat, A.; Subbarayan, G.
Highlights: Numerical techniques for simulation of arbitrary crack path deflection at an interface. Isogeometric analysis with behavioral as well as material enrichments. Simulations of crack path deflection in semiconductor dielectric stacks. Abstract: The competition between crack deflection along the interface or penetration across the interface is numerically modeled in this paper using two novel, isogeometric, numerical approaches. In the first, cracks are modeled as discontinuous enrichments defined isoparametrically on lower dimensional geometrical entities and composed with underlying continuous behavioral approximation. In the second approach, the underlying material description is enriched with a cohesive damage description whose stiffness is evolved according to a prescribed damage law. An automatic crack propagation algorithm is developed for simulating fracture in layered structures, which is demonstrated on a practical, multilayered example problem derived from the semiconductor industry.